MEASURING PREPAREDNESS OF MBBS STUDENTS TO THE CLINICAL EXPOSURE DURING COVID-19 PANDEMIC - Khan, Humaira Fayyaz; Sadiq, Tahira; Khan, Rehan Ahmed; Kamal, Daniyal Ahmed; Ali, Shabana; Yasmeen, Raheela (Pakistan Armed Forces Medical Journal, 2020)
Objective: To measure the level of preparedness of MBBS students to clinical exposure to COVID-19 pandemic.Study Design: Cross-sectional online questionnaire survey.Place and Duration of Study: Physiology Department, Islamic International Medical College, Riphah University, from July to July 2020.Methodology: Medical students from first to final year were included. Data was collected through a validated questionnaire measuring knowledge, attitude and practice of medical students regarding COVID-19. Statistical analysis was done on Microsoft Excel. Frequencies, percentages, mean, and Standard deviation were calculated.Results: A total of 315 students were included in the final analysis. The mean age of the students was 21 3.2. Social media were the main sources of information for 45.5% of the students. The overall level of knowledge of students about COVID-19 was good in 88% and 12% had poor knowledge. The attitude had a mixed response of 55.5% being confident that the disease would be controlled while 93.3% and 87% of the students wanted to help and educate the society. Regarding practice 91% of the students had good practice and used face masks though poor practice were the application of hand sanitizer and going out of home 68%.Conclusion: The level of preparedness of MBBS students before clinical exposure to the COVID-19 Pandemic was satisfactory. The students had good knowledge, a mixed attitude and good practices regarding COVID-19. Gaps in knowledge and the practice which were highlighted need to be addressed by the educational institutes through awareness programs before interaction with the patients is initiated.